Alcohol Treatment Goal Choice Predicts Longitudinal Drinking Outcomes in Adolescent Substance Users. Issue 1 (2nd January 2018) - Buckheit, Katherine; Moskal, Dezarie; Spinola, Suzanne; Maisto, Stephen A.; Chung, Tammy
ABSTRACT: Social cognitive theory suggests when individuals select their own goals, they work harder to achieve them and experience increases in self-efficacy. Research in adults with alcohol use disorder supports the utility of treatment goal choice in predicting longitudinal outcomes; a total abstinence (TA) goal choice has been associated with better clinical outcomes versus a controlled use goal choice. Research on goal choice in adolescent substance users has not been reported. Data from 110 adolescents were collected upon admission to outpatient substance use disorder treatment. Hierarchical linear regressions tested baseline goal choice as a predictor of drinking outcomes at 6-, 12-, and 24-month follow-ups. Goal choice significantly predicted drinking outcomes at 12-month follow-up, but not at 6- or 24-month time points; TA was associated with better clinical outcomes. These findings suggest that goal choice may have clinical utility as a predictor of alcohol use disorder clinical course in adolescents.